1977
DOI: 10.1111/j.1365-2265.1977.tb03328.x
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen‐progestogen Oral Contraceptives and Urinary Calcium Excretion

Abstract: To examine the effects of age and use of oestrogen-progestogen oral contraceptive agents (OCA) on urinary calcium excretion, 24 h urine collections were obtained from 525 women aged 16-69 years during a health survey, and measurements made of the amounts of calcium, creatinine, sodium, potassium and magnesium excreted. Younger women using OCA excreted more potassium and creatinine but less calcium, and less calcium and magnesium relative to creatinine, than corresponding controls using no OCA. Older women excr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Hyperthyroid state was induced by daily sc injections of L-thyroxine (T4, 75 pg/lOOg body wt in 0.3 ml of 0.9% NaC1) for 10 days (25). Similar treatments have been shown to effectively alter thyroid state (24,26). Control and hypothyroid rats received daily sc injections (0.3 ml) of saline.…”
mentioning
confidence: 97%
“…Hyperthyroid state was induced by daily sc injections of L-thyroxine (T4, 75 pg/lOOg body wt in 0.3 ml of 0.9% NaC1) for 10 days (25). Similar treatments have been shown to effectively alter thyroid state (24,26). Control and hypothyroid rats received daily sc injections (0.3 ml) of saline.…”
mentioning
confidence: 97%
“…In future studies, it may be beneficial to allow a far longer period of acclimatisation to a balanced and adequate diet than was practical in this preliminary experiment. Peripheral blood profiles of pmgesterone and oestradiol follow similar patterns in the cycling mare to those seen in women (Ginther 1979;Prior 1990) where studies have shown that administration of oestrogen andor progestagens, during various stages of the reproductive cycle, can cause alterations in the %FE ratios of Ca and Mg (Goulding and McChesney 1977). Progesterone is generally considered to be a 'sodium-losing' steroid or an 'aldosterone antagonist' (Morimoto et al 1992) and it influences the metabolism of both sodium and potassium in women (Michaelakis et al 1971).…”
Section: Discussionmentioning
confidence: 60%
“…Several authors have reported use of OCs by women of young adulthood through to perimenopause may have a beneficial effect on bone-mineral density (BMD) [99-102] through reducing short and long term calcium excretion [103][104][105]. However, again this has not been reported by all investigators with some suggesting age at first use [106], physical activity and race [107] might be major factors affecting this relationship.…”
Section: Calciummentioning
confidence: 99%